A groundwater system in a mountain environment (Serra da Estrela, Portugal) - Marques, J. Espinha (2011)
Mountains are often recognized as the "world's water towers", due to their exceptional ability to generate water resources or good quality and. frequently, or considerable economic value (e.g. UNESCO IHP-VI Programme: http://www,unesco.org, Aureli 2002).